The impact of the COVID-19 pandemic in Brazil: a study in tertiary dental care - João Mykael Alves XAVIER; Ramon Targino FIRMINO; Igor Figueiredo PEREIRA; Myllena Alves XAVIER; Mário César Furtado da COSTA; Renata de Souza Coelho SOARES; Ana Isabella Arruda Meira RIBEIRO (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The pandemic caused by coronavirus has resonated throughout different levels of health care in Brazil and, in this context, the present research aimed to evaluate this impact on tertiary dental care provided by the Unified Health System (SUS). Therefore, an ecological study was conducted with data obtained from the Hospital Information System processed by the Portal of the Department of Informatics of SUS. The sample consisted of patients of all sexes and age groups, whose Hospital Admission Authorizations (AIHs) were approved for dental tertiary care procedures from January 2015 to December 2020. Descriptive analyses and the ANOVA test with a significance level set at p < 0.05 were used. When the annual mean numbers of AIHs approved were evaluated, findings showed that on an average, the Southeast region authorized a higher number of procedures (p-value < 0.001), however, in the pandemic year (2020), a reduction of approximately 24.5% of these hospitalizations occurred throughout Brazil, with the Midwest being the region most affected (32.12%). A percentage increase occurred in the Surgical Treatment of Oral sinus/Oral nasal Fistula (16.1%), in addition to a significant decrease in performing procedures for Resection of Mouth Lesion (33.4%). In the pandemic year, there was a reduction of 14% in expenditures related to hospital services and 23.26% related to professional services. It was concluded that the data presented demonstrated a significant reduction in AIHs for tertiary dental care in the pandemic year.